A REASSESSMENT OF THE TWO POTTERIES AT POMPEII: 1.20.2–3 AND THE VIA SUPERIOR - McCallum, Myles; Theodore Peña, J. (Rei Cretariae Romanae Fautorum Acta, 2024)
While the pottery production facilities on the Via di Nocera at 1.20.3 and on the Via Superior have been the subject of archaeological inquiry for quite some time, both merit renewed examination for what they can reveal about the organization of Roman pottery workshops and how pottery production was integrated into the spatial and social fabric of the town at the time of its destruction in AD 79. Indeed, Pompeii provides us with a unique opportunity to understand the relationship in a Roman town between both the manufacture and distribution of pottery on the one hand, and land-use, traffic patterns, labor and resource exploitation on the other.